2-（CRR）2R Parallel Mechanism with Decoupling-reducing Structure and Its Kinematics Analysis - Junkun Hong; Linxian Che; Li Du; Shikun Wen; Guowang Chen (Jixie chuandong)
A new kind of parallel mechanism is proposed， which can realize three mobile one rotation （3T1R）， and it’s a perfectly symmetrical parallel mechanism of the 4-CRU branch， and then its four branched chains are identical in structure. Based on the theory of SOC and the principle for the structure coupling-reducing， structural decoupling design of 4-CRU parallel mechanism is carried out， and a new 2-（CRR）2R type parallel mechanism with lower coupling degree of κ=1 is proposed. And the advantage of it is that the dynamic platform is composed of two chains in parallel， the angle of the mechanism is relatively large. The coupling degree of 2-（CRR）2R parallel mechanism is reduced to 1， which greatly reduced the difficulty of the positive solution of mechanism position and is conducive to the kinematics analysis. Based on the geometry and motion constraints， the one-dimensional search model of the position positive solution is established， then all the high precision position positive solutions are obtained by the golden section method. The inverse solution equation of the mechanism position is derived， and the correctness of the positive and negative solutions is verified by numerical examples. The velocity and acceleration of the moving platform are analyzed by vector method， the velocity and acceleration of the mechanism are obtained， and the numerical calculation is carried out by MATLAB. At the same time， simulation verification is carried out in Adams， the correctness of the degree of freedom analysis is verified. The kinematics analysis curve is consistent with the MATLAB calculation results， indicating that the analytical model and analysis method established in this paper is correct and feasible.